Green Synthesis and Antibacterial Activity of Silver Nanoparticles: A Review - Asep Bayu Dani Nandiyanto; Annisa Moza Nabila; Faradhina Salfa Nindya; Nur'aini Berliana; Nur Shafa Oktaviani; Selmi Fiqhi Khoiriah; Tedi Kurniawan (Walisongo Journal of Chemistry, 2022)
The purpose of this study was to determine the effect of silver nanoparticles (AgNPs) from different green synthesis medium and their various particle sizes on antibacterial activity. The article review method compares the results of 11 studies obtained from the PubMed database, Web of Science, and ScienceDirect indexed by Scopus in the last five years. The search was conducted based on the phrases nanoparticles, antibacterial, Green synthesis, and AgNPs. Green synthesis of AgNPs with various plant extracts produces different sizes of nanoparticles. The smallest size AgNPs were obtained in the range of 5-15 nm and an average of 13 nm extracted using the leaves of the Pacific Yew tree (Taxus brevifolia). Meanwhile, AgNPs with the best antibacterial effectiveness were obtained from the Blume flower extract (Wedelia urticifolia) measuring less than 30 nm providing a zone of inhibition for S. aureus, K. pneumoniae, E. coli, and P. aeruginosa bacteria.